BALANCING WHOLE-SCHOOL AND SPECIALIST APPROACHES: “BEST PRACTICE” FOR REFUGEE LITERACY EDUCATION BETWEEN 2006 AND 2020 - Spratling, Harrison James (International Journal of Educational Best Practices, 2024)
Arguably the most important aspect of education for students from refugee backgrounds is literacy, so it is important for educators to be aware of best-practice approaches to literacy education for these students. By analyzing themes of best practice for refugee literacy education found in pre- and post-2011 academic literature, this study aims to detect shifts in what academics deem to be “best practice” in this field over time. The study finds evidence of a general shift towards holistic education as best practice for refugee literacy education; however, specialized intervention has grown in emphasis amongst academics focusing on non-classroom interventions such as mental health support and pre-mainstream literacy courses. This means schools and educators must maintain robust connections with external service providers and continuously improve their own professional practice in line with current best-practice pedagogies.